Can seniors spot deepfakes? A diary study of deepfake identification strategies - Chun, Rachel Wan Ying (2025)
Deepfake identification research currently lacks focus on seniors. We address this gap through a diary study to elicit seniors' deepfake identification strategies over three weeks. Results indicate that seniors performed well in identification performance, and over time, were able to integrate multiple strategies, enhancing identification accuracy. Implications of our work are discussed.